Analysis of Work Discipline in Ayam Geprek Sriwedari Karawang Employees - Yulandari; Enjang Suherman; Dwi Epty Hidayaty (Research in Management of Technology and Business, 2024)
This study was carried out at Ayam Geprek Sriwedari Karawang with the objective of analyzing the employees’ work discipline at the establishment. Work discipline plays a crucial role in human resources by enhancing performance in terms of productivity, resource utilization, service, and quality, ultimately leading to the achievement of primary objectives. Effective work discipline yields higher employee productivity and increased business earnings. The objective of this study is to assess the level of work discipline among employees at Ayam Geprek Sriwedari Karawang. The research employed a descriptive methodology that primarily focuses on qualitative research. Data collection strategies involved conducting interviews and observations of the business owner of Ayam Geprek Sriwedari Karawang. The research use the qualitative descriptive analysis method for data analysis. The findings of this study indicate that the work discipline of employees at Ayam Geprek Sriwedari Karawang is satisfactory, as evidenced by four indicators. However, the indicator measuring attendance frequency still needs improvement. Therefore, it is imperative for business owners to allocate greater focus and enforce stringent penalties for any employee who fails to adhere to the designated arrival and departure times.